2020
DOI: 10.1002/nop2.682
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Persian version of Instrument of Professional Attitude for Student Nurses (IPASN)

Abstract: Aim To evaluate nursing students’ professionalism attitude, it is necessary to use a validated and reliable instrument. Design This study aimed to develop the Persian version of the eight‐dimensional professionalism attitude questionnaire for student nurses (Instrument of Professional Attitude for Student Nurses). Methods In this cross‐sectional study during March to April 2017, after being translated into Persian and receiving experts’ comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Psychometric properties of the 28-item Persian version of Instrument of Professional Attitude for Student Nurses (IPASN) showed reliability of 0.89. 21 In contrast to our study, Persian study reported that three out of six domains of ABIM construct can be used to define professionalism in Iranian context. 22 Limitations: Data was collected from only one institute and only from one year (Year four MBBS) of undergraduate medical students.…”
Section: Discussioncontrasting
confidence: 82%
“…Psychometric properties of the 28-item Persian version of Instrument of Professional Attitude for Student Nurses (IPASN) showed reliability of 0.89. 21 In contrast to our study, Persian study reported that three out of six domains of ABIM construct can be used to define professionalism in Iranian context. 22 Limitations: Data was collected from only one institute and only from one year (Year four MBBS) of undergraduate medical students.…”
Section: Discussioncontrasting
confidence: 82%
“…Internal consistency calculation (Cronbach's alpha) was used to estimate reliability. [ 19 20 ] The results of the test-retest indicated that the intra-class correlation coefficient was appropriate, and the reliability of this 14-item scale was confirmed in Iranian caregivers. The limitation of this study is both factor analyses was performed on one sample size.…”
Section: Discussionmentioning
confidence: 93%
“…The literature indicated that the item with factor loading and item scale correlation <0.30 should be excluded from the scale. [ 19 20 21 ] Therefore, we excluded item 13, and the results showed that it fitted better. In the result of RMSEA, it was moderate, however, Goodness of Fit Statistics for other items was good and in the expected level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation